Women’s Empowerment in Agrifood Governance (WEAGov): An Assessment Framework - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
WEAGov is an assessment tool developed by the International Food Policy Research Institute (IFPRI) and partners to measure women’s voice and agency in national-level policymaking in the agrifood system. Women’s voice within policymaking is key for ensuring that women can exercise control over the policy decisions that affect their lives, as well as for advancing Sustainable Development Goals and ensuring equity. By providing a way to assess women’s voice in the agrifood policy process, WEAGov helps to identify opportunities to close the gender representation gap and provides a way to monitor progress in women's empowerment in agrifood systems governance over time. WEAGov looks across three parts of the policy cycle (1) policy design; (2) policy implementation; and (3) policy evaluation. The policy design component focuses on how different policy problems rise to the policy agenda, how policy solutions are formulated and designed, and how and whether policy solutions are adopted. The policy implementation component looks at how policies are implemented in practice, including budgetary outlays and organizational strategies for the delivery of services. Finally, the policy evaluation component considers how policies are assessed against their objectives and initiates reforms.